Al-Muhawalah li Tarqiyati Maharati al-Qira’ah fi al-Mawadd al-‘Arabiyyah bi Istiratijiyyati Jigsaw - Ani (AlFaqrah: Journal of Arabic Language Teaching, Linguistics and Literature, 2026)
There are problems among students who experience difficulties in reading and understanding the content of reading texts. This is because students are rarely trained to translate reading texts, and the teaching methods used tend to be less varied and monotonous. Therefore, this study investigates whether the use of the Jigsaw method can improve Arabic reading skills among eighth-grade students of class VIII “C” at the Islamic Girls’ Junior High School of Al-Ittihad Ummah, Telag, in the 2024/2025 academic year. Based on the background and formulation of the problem above, the purpose of this study is to determine the implementation of the Jigsaw method in improving Arabic reading skill materials for eighth-grade students of class VIII “C” at the Islamic Girls’ Junior High School of Al-Ittihad Ummah, Telag, in the 2024/2025 academic year. The research method used is Classroom Action Research conducted in two cycles. Data were collected through observation, tests, and documentation techniques. The research results show that in the pre-cycle stage, 14 students met the minimum achievement criteria, while 16 students did not meet the minimum achievement criteria, with an average score of 50.3. In the first cycle, 21 students met the minimum achievement criteria, while 9 students did not, with an average score of 69.8. Furthermore, in the second cycle, 25 students met the minimum achievement criteria, while 5 students did not, with an average score of 78.7. These results indicate an improvement in students’ reading skills.